Бытовые системы очистки, увлажнения, обеспыливания и обеззараживания воздуха - Бордунов В. В.; Ситников А. С.; Дмитриев В. С. Виктор Степанович; Гладышев Г. Н.; Белявин М. Л.; Соболев И. А.; Бордунов С. В.; Васильева О. Л. (2000, 2000)
В фонде НТБ ТПУ отсутствует